Comparative Analysis, Problems and Realization of Remote HR-Management in Russia and Abroad - Sergey TINKOV; Igor FILKEVICH; Elena TINKOVA (Communications of International Proceedings, 2021)
The article describes domestic and foreign labour markets statistics concerning remote work vacancies and also analyses the domestic practice of arranging remote workplaces, its special features and effectiveness in the midst of COVID-19. The article also describes the attitude of local employers towards telework and the possibilities for improving domestic practice of HR-management via organizing remote work places with applying successful experience of foreign partners. Telework is not synonymous to distance work and freelance (home-based work). Home-based work implies employees performing their job functions at home by means and tools that they acquire at their own expense, whereas distance working means performing work duties outside the place which is under direct or indirect control of employer.
Keywords: Management; Personnel; Teleworking; Labor Market; Remote Workplace Organization.